MARKETING INFORMATION SYSTEM FOR PURCHASING BOOKS FOR LIBRARY; ASSISTING BUSINESS BUYING BEHAVIOR IN EDUCATIONAL INSTITUTION - Harianto Kristanto (Duta Wacana Christian University, 2008)
Purchasing books for library in educational institution has many problems. The librarians as buyers can not buy books since she/ he does not have sense about the contents and objective of the needs. Students and lectures know better and morecapable to selecting books they need, but they do not have support from marketing database or marketing information system. A marketing information system was analyzed and designed to assist librarians, lectures, students to communicate each other. The librarians make segmentation about categorized books, budget segmentation by topics, study program, faculties, and major interest. This study propesed a design and a user interface to make a comfortable and precise decision in purchasing books. CRM concepts will be used as a communicating between the librarians and the users.